The study of antibacterial activity of some plant extracts against causes of pneumonia - Baghdad Science Journal (مجلة بغداد للعلوم, 2011)
Eighty five samples were taken from patients suffering from pneumonia. Seventy-eight isolates were diagnosed as following: Staphylococcus aureus (23), klebsiella pneumoniae (29), Streptococcus pneumoniae (15), Serratia sp. (4), Haemophilus influenzae (4) and Pseudomonas aeruginosa (3). The clinical isolates were tested for antibiotics sensitivity. They appeared highly resistance to penicillin G and Ampicillin at percentage 89.7 and 84.6% respectly while the results showed highly sensitivity to streptomycin at percentege of (12.8%). To study the antibacterial activity of Alium sativum, Eucalyptus microtheca leaves and Cydonia oblonga seeds extracts, five multi resistant strains were used by using agar well diffusion and disk methods at concentrations of (24, 12, 6, 3)%. The agar well diffusion was prefered for both of Alium sativum and Eucalyptus microthesca extracts while both methods were prefered for Cydonia oblonga extract by measuring inhibition zones .The results showed antibacterial activity of Alium sativum on S.aureus and S. pneumoniae at concentration 3-24 % and for klebsiella pneumoniae at concentration of 6-24%While it was 12-24%for Serratia sp. and Pseudomonas aeruginosa. Eucalyptus microtheca extracts showed antibacterial at concentration of 24-3%for S.aureus, S. pneumoniae and Ps. aeruginosa. While K. pneumoniae and Serratia sp sensitive at concartatins of 24%. The ethanol and oil extracts of Cydonia oblonga seeds had anti bacterial activity at all concentrations for all strains except Serratia sp. showed sensitivity at concentrations of 24-6%for both extracts.